Legalisasi RUU Anti Pornografi dan Pornoaksi Dalam Perspektif Strategi Dakwah - Sahlan, Muhammad (Musawa Jurnal Studi Gender dan Islam, 2006)
RUU Anti Pornography and Pomoaksi still in course of solution in DPR. At the same time many respon from various society component, both for pros and also counter. Have to be confessed that problem of pornography and pomoaksi not solely social problem, more than that - in eye glasses missionize also represent the religious problem. As nation which its resident majority Moslem people, have become the obligation for the "nahi of munkar" by following to support to ratifying of the RUU till become UU. This article study the process legalize the RUU of Pornography and Pomoaksi in perpective of dakwah strategy. In perpective of dakwah strategy, if the RUU become a I.aw so that have the consequence punish, hence pornography and pomoaksi will lose from circulation, doing an injustice of kesusilaan will decrease, standing and prestige of woman clan not flatter the, behavior, moral and personality of Indonesian nation will be saved. Though have to be confessed that the RUU still many insuffiency, among others not yet fair in seeing relationship of men and woman.